Safety of Drinking Water from Primary Water Sources and Implications for the General Public in Uganda - Kasozi, Keneth Iceland; Namubiru, Sarah; Kamugisha, Roland; Eze, Ejike Daniel; Tayebwa, Dickson Stuart; Ssempijja, Fred; Nshakira, Nathan (Journal of Environmental and Public Health, 2019)
There is scarcity of information about the quality and safety of drinking water in Africa. Without such vital information, sustainable development goal number 6 which promotes availability and sustainable management of water and sanitation remains elusive especially in developing countries. The study aimed at determining concentrations of inorganic compounds, estimated daily intake (EDI), target hazard quotient (THQ), hazard index (HI), incremental lifetime cancer risk (ILCR), and identify safe drinking water source sources in Southwestern Uganda. Methods. This was an observational study in which 40 drinking water samples were collected from georeferenced boreholes, springs, open wells, bottled, and taps within Bushenyi district of Southwestern Uganda. Water samples were analyzed for copper (Cu), iron (Fe), zinc (Zn), lead (Pb), cadmium (Cd), and chromium (Cr) levels using atomic absorption spectrometry (AAS). Water safety measures (EDI, HI, and ILCR) were established for each water source and compared with local and international water permissible standards for each analyte. A spatial map was drawn using qGIS®, and analysis of quantitative data was done using MS Excel 2013 at 95% significance. Results. Heavy metals were present in the following order: 11.276 ppm > 4.4623 ppm > 0.81 ppm > 0.612 ppm > 0.161 ppm for Fe, Zn, Pb, Cu, and Cd, respectively, while Cr was not detected. Fe was the primary water heavy metal in the order of open well > borehole > tap > spring > bottled water. This was followed by Zn levels in the order of tap > bottled > spring > borehole > open well. All compounds were within international water safety standards except Pb. Hence, there is need for the government of Uganda to establish water filtration systems, particularly for Pb to improve the quality of water for the general public. The EDI was similar () for water consumed from spring, bottled, and tap sources for Fe and Zn levels. Similarly, no differences were found in the EDI for children and adults . Furthermore, the HI showed an absence of noncarcinogenic risk associated (HI < 1), although the ILCR was higher in adults than children due to high Cd concentrations. The current identified Fe is a major heavy metal in drinking water of Uganda, and boreholes were the major safest sources of drinking water identified in this study.